Interpreters as Vital (Re)Tellers of China’s Reform and Opening-Up Meta-Narrative: A Digital Humanities (DH) Approach to Institutional Interpreters’ Mediation - Gu, Chonglong (Frontiers in Psychology, 2022)
If the important role of written translation in the construction and contestation of knowledge and narratives remains largely under-explored, then the part played by interpreting and interpreters is even less examined in knowledge construction and story-telling. At a time when Beijing increasingly seeks to bolster its discursive power and have the Chinese story properly told, the interpreter-mediated and televised Premier-Meets-the-Press conferences constitute a typical discursive event and regime of truth (Foucault 1984) in articulating China’s officially sanctioned ‘voice’. Discursive in nature, the institutionalised event permits Beijing to construct a desired version of truth, fact and narrative in front of the more vociferous and dominant West. As an attempt to employ digital humanities (DH) methods to real-world language use, this corpus-based CDA study explores the press conference interpreters’ agency and mediation in rendering key concepts and discourses (e.g., ECONOMY and REFORM) constitutive of the broader Reform and Opening-up meta-narrative, which legitimises China’s political and economic systems, developments, policies and positions in the post-1978 era. The interpreters are found to maintain and often further reinforce Beijing’s discourse in English at various levels. Apart from indicating issues of institutional alignment, this study points to interpreters’ agency in communicating beyond national borders, (re)constructing political and institutional knowledge, counterbalancing the naturalised and taken-for-granted Western narratives (Said 1978; Shi-xu 2014), and contributing to the shifting East-West power differentials discursively. This study highlights the significance of interpreters as indispensable (re)tellers of the Chinese story in an increasingly mediat(is)ed world, where the interpreted discourse is routinely quoted verbatim on various platforms and taken for granted as the correct version of Beijing’s official ‘voice’